2019
DOI: 10.1016/j.isci.2019.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteome Landscape of the NCI-60 Cancer Cell Lines

Abstract: SummaryHere we describe a proteomic data resource for the NCI-60 cell lines generated by pressure cycling technology and SWATH mass spectrometry. We developed the DIA-expert software to curate and visualize the SWATH data, leading to reproducible detection of over 3,100 SwissProt proteotypic proteins and systematic quantification of pathway activities. Stoichiometric relationships of interacting proteins for DNA replication, repair, the chromatin remodeling NuRD complex, β-catenin, RNA metabolism, and prefoldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 88 publications
(183 reference statements)
4
84
0
Order By: Relevance
“…However, no structural data at any resolution have been presented for the intact complex. The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.…”
Section: Ino80mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no structural data at any resolution have been presented for the intact complex. The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.…”
Section: Ino80mentioning
confidence: 99%
“…Some structural information is available for portions of the NuRD complex ( Figure S1b): (i) HDAC1 forms a 2:2 complex with an N-terminal segment of MTA1 (MTA1 162-335 -the ELM-SANT region) (27); (ii) single particle electron microscopy (SPEM) and X-ray crystallography data show that two copies of RBBP4 can bind the C-terminal portion of MTA1 (28-30); (iii) MBD2 and GATAD2A form a heterodimeric coiled-coil (24, 31); and (iv) a cryo-EM structure has been determined for the complex between the catalytic domain of CHD4 and a nucleosome particle (32).However, no structural data at any resolution have been presented for the intact complex. The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.The mechanisms by which NuRD selects target sites are also poorly understood. Transcriptional regulators such as FOG1 (22,39) and BCL11A (40,41) can bind to NuRD via the RBBP subunits but this mechanism is likely to account for only a small proportion of NuRD-genome interactions.Recently, we demonstrated that the chromatin-binding protein PWWP2A, which can selectively recognize H2A.Z-containing nucleosomes (42,43), interacts robustly with the MTA, HDAC and RBBP subunits of NuRD.…”
mentioning
confidence: 99%
“…About ten thousand redundant and low-quality assays were removed. Then we extracted the chromatography of these fragments and MS1 signals using OpenSWATHWorkflow, followed by curation using DIA-expert [106]. Briefly, the chromatography of all fragments and MS1 signals were subject to scrutiny by empirically developed expert rules.…”
Section: Peptide Quantification Using Openswathmentioning
confidence: 99%
“…As a benchmark, we used transcriptomics datasets are from the default dataset from bladderbatch package and ComBat package. We also applied the BatchServer to a published proteomic data of NCI-60 dataset cell lines [17]. The missing values of all the four data sets were replaced by '1'.…”
Section: Illustrative Applications Of Batchsevermentioning
confidence: 99%
“…The proteomics data set are from NCI-60 cell lines [17], containing 3,171 proteins and 60 samples of 12 batches. This data set was generated by Pressure Cyling Technology coupled with data independent acquisition (PCT-DIA) [18].…”
Section: Illustrative Applications Of Batchsevermentioning
confidence: 99%